Empowering Pasifika Students to Express their Identities through Visual Arts in New Zealand Secondary Schools: The Role of Euro-descendent Teachers - Smith, Jill Elizabeth (International Journal of Multicultural Education, 2016)
The greatest numbers of young people in New Zealand are from Pasifika peoples’ ethnic groups. In contrast, art teachers in secondary schools are predominantly European. Research conducted in 2015, which investigated how art teachers are responding to the increasing diversity of students, uncovered important insights. This article provides “snapshots” of how four European-New Zealand art teachers, who work in schools where Pasifika students comprise the largest ethnic group, are empowering them to express themselves within their cultural milieu. Articulated through the voices of the art teachers, the stories of these students are visualized through examples of their art works.